2016
DOI: 10.1007/s00167-016-4231-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of home-based exercises versus individualized supervised outpatient physical therapy programs after total knee arthroplasty: a systematic review and meta-analysis

Abstract: Purpose The aim of the present study was to evaluate the efficacy and safety of non‐supervised home‐based exercise versus individualized and supervised programs delivered in clinic‐based settings for the functional recovery immediately after discharge from a primary TKA. Methods Medline, Embase, Cochrane, and PEDro databases were screened, from inception to April 2015, in search for randomized clinical trials (RCT) of home‐based exercise interventions versus individualized and supervised outpatient physical th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 36 publications
(86 reference statements)
0
40
0
1
Order By: Relevance
“…For example, authors of a study demonstrated that HEP and supervised exercises were equally effective in short term improvements in physical function and knee range of motion after total knee replacement at equivalents costs for patients with after total knee replacement [24]. Their study was based on a meta-analysis that had significant statistical heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, authors of a study demonstrated that HEP and supervised exercises were equally effective in short term improvements in physical function and knee range of motion after total knee replacement at equivalents costs for patients with after total knee replacement [24]. Their study was based on a meta-analysis that had significant statistical heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Functional rehabilitation, an important measurement to evaluate a successful TKA surgery, often takes few months, if not, years. Physical therapy plays an integral role in promoting functional rehabilitation following TKA, which could signi cant improvements were observed in function, quadriceps strength, and length of stay [8][9][10]. After the surgical procedure, early and su cient rehabilitation programs, including physical therapy, will be greatly helpful to restore the function and range of motion (ROM) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Physical therapy plays an integral role in promoting functional rehabilitation following TKA, which could signi cant improvements were observed in function, quadriceps strength, and length of stay [8][9][10]. After the surgical procedure, early and su cient rehabilitation programs, including physical therapy, will be greatly helpful to restore the function and range of motion (ROM) [10]. These rehabilitation programs or physical therapy could and should be continued after hospital discharge [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiotherapy exercise provided at home is an appealing approach with the possibility of wider acceptability and uptake in the near future [9]. Studies have shown that standardized home programs were not inferior to inpatient or outpatient physiotherapy in regard to their effects on functional status, health related quality of life (HRQOL) and range of movement (ROM) of the operated joint [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%